Efficacy of sofosbuvir as treatment for yellow fever: protocol for a randomised controlled trial in Brazil (SOFFA study). Issue 11 (25th November 2019) - Figueiredo-Mello, Claudia; Casadio, Luciana Vilas Boas; Avelino-Silva, Vivian Iida; Yeh-Li, Ho; Sztajnbok, Jaques; Joelsons, Daniel; Antonio, Marilia Bordignon; Pinho, João Renato Rebello; Malta, Fernanda de Mello; Gomes-Gouvêa, Michele Soares; Salles, Ana Paula Moreira; Corá, Aline Pivetta; et al.
Abstract : Introduction: An ongoing outbreak of yellow fever (YF) has been reported in Brazil with 1261 confirmed cases and 409 deaths since July 2017. To date, there is no specific treatment available for YF. Recently published papers describing in vitro and animal models suggest a potential effect of antiviral drugs (approved for the treatment of hepatitis virus) against flaviviruses, including YF. The primary aim of this study is to analyse the effect of sofosbuvir on viral kinetics and clinical outcomes among patients presenting with YF. This is a multicentre open-label randomised controlled trial with 1:1 individual allocation, stratified by severity and by recruiting centre. Methods and analysis: Adults with suspected or confirmed YF infection and symptoms lasting up to 15 days are screened. Eligible and consenting patients are randomised to receive oral sofosbuvir 400 mg daily for 10 days or to receive standard clinical care. Viral kinetics are measured daily and the reduction in YF plasma viral load from the sample at inclusion to 72 hours after randomisation will be compared between active and control groups. Clinical outcomes include severity meeting criteria for intensive care support, liver transplantation, in-hospital mortality and mortality within 60 days. Ethics and dissemination: Ethics approval was obtained at the participating sites and at the national research ethics committee (CAAE 82673018.6.1001.0068). The trial has been submitted for ethical approval at additional potential recruiting centres. Results of the study will be published in journals and presented at scientific meetings. Trial registration: Brazilian Clinical Trials Registry (RBR-93dp9n).